Gold(I)-catalyzed domino reaction of allyl 2-en-4-ynyl ethers to 1,3,6-trien-4-yl ketones - Hashmi, A. Stephen K.; Graf, Katharina; Ackermann, Martin; Rominger, Frank (ChemCatChem, 2013)
The gold(I)-catalyzed reaction of allyl 2-en-4-ynyl ethers provides stereoselectively (Z)-1,3,6-trienes with an acyl substitutent in the 4-position. The reaction proceeds through an oxygen transfer along the chain and a clean allylic inversion. This complements the preceding work by Gagosz, who obtained furan derivatives in his investigation of similar substrates with terminal alkynyl groups.10, 16 The only drawback of this mechanistically new pathway is the instability of the products under the reaction conditions, which sometimes prevents their isolation in high yields.
Gesehen am 08.10.2021